Pengembangan Smart Air Condition Control Menggunakan Platform Blynk Berbasis Mikrokontroler ESP8266 dan Sensor DHT11 - Ade Putera Kemala; Muhammad Edo Syahputra; Henry Lucky; Said Achmad (Bina Nusantara University, 2022)
Air Conditioners (AC) are increasingly used to get the room temperature as desired, starting from home use to keep the room cool and enjoyable, to specific room like server rooms or ATM which are focused on keeping the room cool in order to keep the equipment cool. The role of AC is quite important to maintain room temperature, and its increasing use has led to the growing need for users to control the AC. The Internet of Things allows users to remotely control air conditioners using the gadgets used and get real time room temperature information. The AC control system based on Internet of Things (IoT) utilizes an internet connection to monitor room temperature and control AC remotely. The devices used are DHT11 as a temperature sensor to get room temperature, Infrared Receiver to read the code sent by the remote AC, Infrared Transmitter to send commands to the AC in the room, and ESP8266 as a microcontroller and a link to the internet. The IoT platform used is Blynk which has the ability to access the microcontroller from the user's gadget. The tests are running on room air conditioners such as the Panasonic CS-PC18PKP series, the Panasonic CS-YN18TKP series and the Samsung AR09TGHQASINSE series. The test results showed that the room air conditioner was successfully controlled, and the room temperature was read in real time via an android smartphone.